Pension funds and stock market volatility: An empirical analysis of OECD countries - Thomas, Ashok; Spataro, Luca; Mathew, Nanditha (Journal of Financial Stability, 2014)
The paper explores the empirical relationship between the share of pension funds assets invested in stocks and stock market volatility in OECD markets. For this purpose, by using panel data of 34 OECD countries from 2000 to 2010, we estimate both a random-effects panel model and a Prais–Winsten regression with panel-corrected standard errors and autoregressive errors. The estimations document that there is a significant negative relationship between the share of pension funds assets invested in stocks and stock market volatility in OECD markets. The binary probit and logit models further validate the argument that pension funds as institutional investors can dampen stock market volatility.